Novel unit B cryptophycin analogues as payloads for targeted therapy - Figueras, Eduard; Borbély, Adina; Ismail, Mohamed; Frese, Marcel; Sewald, Norbert (Beilstein Journal of Organic Chemistry, 2018)
Cryptophycins are naturally occurring cytotoxins with great potential for chemotherapy. Since targeted therapy provides new perspectives for treatment of cancer, new potent analogues of cytotoxic agents containing functional groups for conjugation to homing devices are required. We describe the design, synthesis and biological evaluation of three new unit B cryptophycin analogues. The O-methyl group of the unit B D-tyrosine analogue was replaced by an O-(allyloxyethyl) moiety, an O-(hydroxyethyl) group, or an O-(((azidoethoxy)ethoxy)ethoyxethyl) substituent. While the former two maintain cytotoxicity in the subnanomolar range, the attachment of the triethylene glycol spacer with a terminal azide results in a complete loss of activity. Docking studies of the novel cryptophycin analogues to β-tubulin provided a rationale for the observed cytotoxicities.
Keywords: cryptophycin; cytotoxic agents; novel payloads; tubulin inhibitors; tumour targeting